Post-natal functional abilities and its association with depression following cesarean section: a cross-sectional study - Seah, Yi Shean (2024)
Background: Postpartum depression (PPD) is common among postnatal women. The prevalence of PPD is higher in cesarean section compared with vaginal delivery. Although PPD has various causes, there is insufficient research on how functional abilities after delivery and its association of the development of PPD following cesarean section. Most of the studies were conducted separately about the prevalence of postpartum depression and the prevalence of functional disabilities in postpartum women. Thus, it is crucial to explore the association between a woman's functional capabilities during this time and the prevalence of experiencing depression following cesarean section.